Application go-sport as a solution to search information on facilities, places, partners, and sports events for students - Rofik, Rofik; Anggraini, Tasya Fitria; Prasetiyo, Budi; KA, Cecep Bagus Suryadinata (SHM Publisher, 2023)
Sport is a physical and mental activity that is beneficial for people to maintain the body and develop the quality of health. This makes exercise an activity that needs to be done for everyone to maintain their stamina. However, the lack of information about places, facilities, partners, and sports events is a strong reason in terms of reducing student motivation in carrying out sports activities themselves. The purpose of this research is none other than to design an application that can help students get all sports information. These things are none other than to foster a strong desire to do sports activities. Through technology smartphone which has been owned by the wider community, this research creates a solution by designing an application called